A disulfide-induced supra-amphiphilic co-assembly for glycosylated pro-drug-photosensitizer nanoparticles in combination therapies. Issue 90 (26th October 2022) - Jin, Wenjuan; Chen, Zelong; Yang, Senyu; Qu, Yun; Pei, Yuxin; Pei, Zhichao
Abstract : We reported an intermolecular chalcogen bonding interaction (S⋯S contacts) induced supra-amphiphilic co-assembly strategy to construct glycosylated pro-drug-photosensitizer nanoparticles (BG-L NPs) in combination therapies. Abstract : A disulfide-induced supra-amphiphilic co-assembly strategy for hydrophobic drug co-delivery in combination therapies was proposed based on a disulfide bond containing hydrophobic pro-drug-photosensitizer (BG) and a hydrophilic/targeting dimer lactose molecule (Lac-SS-Lac). The anti-tumor efficiency was significantly enhanced by the combination therapies of epidermal growth factor receptor (EGFR) targeted therapy and phototherapy in EGFR-positive and/or galectin overexpressed tumors.